Verrucous Carcinoma of Buccal Mucosa in Female: A Rare Case Report of Traumatic Tooth Origin - V. Keerthi Narayan (Hindawi Limited, 2021)
Verrucous carcinoma or Ackermann's tumor is considered a low-grade variant of squamous cell carcinoma frequently presenting at the oral mucosa and skin. Oral verrucous carcinoma clinically presents as a proliferative or cauliflower-like lesion or as ulceroproliferative lesion on the buccal mucosa followed by other sites such as the gingiva, tongue, and hard palate. Tobacco in both smoking and smokeless form, alcohol, and opportunist viral infections are the most associated etiologies in most of the reported literature cases. Here, in this paper, we discuss a rare case scenario of a 52-year-old female diagnosed with verrucous carcinoma of the left buccal mucosa with constant traumatic irritation caused by tooth as etiology for the occurrence of lesion, though verrucous carcinoma is described as a benign lesion with minimum aggressive potential but long-standing cases have shown transformation into squamous cell carcinoma. Therefore, early diagnosis and surgical excision of the lesion are the most appropriate treatment modality of verrucous carcinoma.